2019
DOI: 10.1302/0301-620x.101b10.bjj-2018-1282.r2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of high-molecular-weight polyethylene core suture tape for intra-articular ligament reconstruction

Abstract: Aims Options for the treatment of intra-articular ligament injuries are limited, and insufficient ligament reconstruction can cause painful joint instability, loss of function, and progressive development of degenerative arthritis. This study aimed to assess the capability of a biologically enhanced matrix material for ligament reconstruction to withstand tensile forces within the joint and enhance ligament regeneration needed to regain joint function. Materials and Methods A total of 18 New Zealand rabbits un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…Recent research showed in histologic analysis that there is no negative effect on bone tunnel healing or a prolonged inflammation period by the use of FiberTape. 23 Furthermore, the biocompatibility of the FiberTape was confirmed as having no synovial reactions, no cartilage damage, or other functional consequences. 24 We subsequently confirmed these findings macroscopically when we performed re-arthroscopies (see Fig 18 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent research showed in histologic analysis that there is no negative effect on bone tunnel healing or a prolonged inflammation period by the use of FiberTape. 23 Furthermore, the biocompatibility of the FiberTape was confirmed as having no synovial reactions, no cartilage damage, or other functional consequences. 24 We subsequently confirmed these findings macroscopically when we performed re-arthroscopies (see Fig 18 ).…”
Section: Discussionmentioning
confidence: 93%
“…There are many studies showing the beneficial biomechanical effect of FiberTape use in ACL repair as well as reconstruction. 19 , 23
Fig 18 Left knee with patient in supine position. Diagnostic Arthroscopy one year after ACL reconstruction shows intact ACL graft (green star) with incorporated FiberTape (blue arrow) and an intact synovial sheath.
…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown that an internal brace increases the biomechanical performance of intra-articular ligament reconstructions and does not affect bone tunnel healing. 17 Using FiberTape also makes it possible to add a second tibial fixation point on the anteromedial cortex of the tibia with a TightRope ABS device. The advantages and limitations of this surgical technique are listed in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Even in vivo animal studies have demonstrated advantages of suture tape constructs over standard sutures. 4 However, a common theme in cadaveric mechanical studies is that failure generally occurs at the tissue interface rather than the suture material or anchor. 3 Thus, although suture material strength is an important component of a repair, the quality and thickness of local tissue must be taken into consideration when determining whether postoperative rehabilitation or return to activities might be adjusted based on repair strength.…”
Section: See Related Article On Page 708mentioning
confidence: 99%